The Reality Of Yamani Athletic And The Means For Developing it - Haqi, Mohammed; Saleh, Hussein (Journal of Physical Education, 2011)
The research focused on Yamani sports in general and athletics in particular . athletics in Yamani is a very resent sport and it started after September revolution . the republic issued a law that athletic should be taught in all Yamani school , clubs , athletic clubs and the military during the seventeenth century . the importance of the study lies in the lack of studies and research that tackle this sport as well as preparing the means for developing athletics is yaman . The research used descriptive method . the subjects were (30) people who are closely in touch with athletics in all Yamani governorates including coaches , federation members , old players and teachers . the research used closed questionnaire and personal interview . the collected data was treated using percentile . finally the researchers concluded many conclusion that develop Athletics in yaman as well as preparing the means for this development